Interior of the Golden Pavilion of Jehol (Max Rigot Selling Co.)
In the center backgound the image of the great Avalokitecvara smiles serenely down upon the worshippers from its stone table. The patron saint of Tibet and protector of its capital, is supposedly reincarnated in the Dalai Lma of Lhasa.